Reconstructing the World Economy - SaKong, Il (International Monetary Fund, 2010)
This volume presents papers from a conference organized by the Korea Development Institute and the IMF. The purpose of this high-level conference was for policymakers and academics from the Asian region and from G-20 countries to discuss forward-looking economic and financial issues of interest to the international community, such as restoring normalcy to fiscal policy, macroprudential regulation, the future of the financial system, global fiscal imbalances, and the international monetary system. Topics include: (1) A strategy for renormalizing fiscal and monetary policies in advanced economies. Key principles for restoring financial stability in the wake of the crisis, including the timing and sequence for exit, are identified. (2) Rethinking macroeconomic policy. This section examines if and how macroeconomic policy should respond to sectoral imbalances and asset-price and housing imbalances, as well as a potential role for macroprudential regulation. (3) Redesigning the financial system of the future. Responses by both policymakers and the private sector to recent events are evaluated in terms of how they will shape the future financial system and its role in the global economy. (4) Global imbalances. The argument is made that there is an urgent need to address the domestic and international distortions that are a key cause of imbalances; failure to do so would threaten the sustainability of the recovery. (5) The future of the international monetary system. Steps that can be taken to address the inherent weaknesses in the current system are described, including possible solutions on both the demand side and on the supply side.